Vascular adenosine monophosphate‐activated protein kinase: Enhancer, brake or both?. Issue 2 (24th November 2019) - Chen, Hui; Vanhoutte, Paul Michel; Leung, Susan Wai Sum
Abstract: Adenosine monophosphate‐activated protein kinase (AMPK), expressed/present ubiquitously in the body, contributes to metabolic regulation. In the vasculature, activation of AMPK is associated with several beneficial biological effects including enhancement of vasodilatation, reduction of oxidative stress and inhibition of inflammatory reactions. The vascular protective effects of certain anti‐diabetic (metformin and sitagliptin) or lipid‐lowering (simvastatin and fenofibrate) therapeutic agents, of active components of Chinese medicinal herbs (resveratrol and berberine) and of pharmacological agents (AICAR, A769662 and PT1) have been attributed to the activation of AMPK (in endothelial cells, vascular smooth muscle cells and/or perivascular adipocytes), independently of changes in the metabolic profile (eg glucose tolerance and/or plasma lipoprotein levels), leading to improved endothelium‐derived nitric oxide‐mediated vasodilatation and attenuated endothelium‐derived cyclooxygenase‐dependent vasoconstriction. By contrast, endothelial AMPK activation with pharmacological agents or by genetic modification is associated with reduced endothelium‐dependent relaxations in small blood vessels and elevated systolic blood pressure. Indeed, AMPK activators inhibit endothelium‐dependent hyperpolarization (EDH)‐type relaxations in superior mesenteric arteries, partly by inhibiting endothelial calcium‐activated potassium channel signalling. Therefore, AMPK activation is not necessarily beneficial in terms of endothelial function. The contribution of endothelial AMPK in the regulation of vascular tone, in particular in the microvasculature where EDH plays a more important role, remains to be characterized.